A narrative inquiry study of two piano teachers’ perceptions on later career creativity and sustainability in music teaching / Lee Wai Kin - Lee , Wai Kin (2019)
This study was aimed to investigate the views and perspective of two piano teachers and music educators in Malaysia on the creativity and sustainability in their later music career. A narrative inquiry study approach was conducted to examine how creativity can be realised through their life stories and professional life experiences. Open ended interview was employed, for the interviewees to describe their professional experiences; from their early years of teaching until today; their significant identities as piano teacher, performer, composer and researcher, their contributions on society with their gifted talent and endeavour are undoubtedly essential. This study investigates how propulsion theory proposed by Sternberg (1999) can be applicable to reflect the creativity and sustainability in their career path and their contribution to the field. The eight different types of creative contribution are as follow: (1) replication, (2) redefinition, (3) forward incrementation, (4) advanced forward incrementation, (5) redirection, (6) reconstruction/redirection, (7) reinitiation and (8) integration. The viable options were proposed based on the current study, and how creative discoveries and knowledge in later-career creativity could be achieved. Furthermore, the participants’ creative integration of teaching, performing, composition and research were discussed. Overall, the result demonstrated that music teaching is a lifelong learning process, only by constantly engaging in it, creativity and sustainability can be realised.